Measurement Invariance of the Prosocial Behavior Scale in Three Hispanic Countries (Argentina, Spain, and Peru) - Martí-Vilar, Manuel; Merino-Soto, César; Rodriguez, Lucas Marcelo (Frontiers in Psychology, 2020)
In a growing context of multiculturalism, prosocial behavior is important to build effective social exchange and service orientation among university students. The present study investigates prosocial behavior from a psychometric approach, to obtain evidence of the internal structure of the prosocial behavior scale (PS), in 737 young people enrolled at universities in Argentina (207), Spain (310) and Peru (220). First, the clarity of the items was explored in the three countries; second, possible irrelevant patterns of response, such as the careless and extreme responses, were evaluated; third, the nonparametric Mokken methodology was applied to identify the basic properties of the scale score; fourth, the structural equation modelling (SEM) methodology was used to identify the properties of the internal structure (dimensionality, tau-equivalence) of the latent construct; fifth, the measurement invariance according to sex (intra-equivalence) and country (inter-equivalence) was examined with the SEM methodology and other complementary strategies. Finally, reliability and internal consistency were evaluated both at score level and at item level. Implications for use of the PS instrument are discussed.